Lack of hypercapnic increase in cerebral blood flow at high blood viscosity in conscious blood-exchanged rats - Lenz, Christian; Rebel, Annette; Bucci, Enrico; Ackern, Klaus van; Kuschinsky, Wolfgang; Waschke, Klaus F. (Anesthesiology, 2001)
The hypothesis of a compensatory dilation of cerebral vessels to maintain cerebral blood flow at a high blood viscosity was tested during hypercapnia in the study after replacement of blood by hemoglobin solutions of defined viscosities. If compensatory vasodilation exists at normocapnia at a high blood viscosity, vasodilatory mechanisms may be exhausted when hypercapnia is added, resulting in a lack of increase in cerebral blood flow at hypercapnia.In conscious rats, blood was replaced by ultrapurified cross-linked hemoglobin solutions that had defined and shear rate-independent low or high viscosities (low- and high-viscosity groups). Blood viscosity differed threefold between both groups (1.2 vs. 3.6 mP x s). Thereafter, rats inhaled either a normal or an increased concentration of carbon dioxide in air. Cerebral blood flow was determined by the iodo[14C]antipyrine method.During normocapnia, global and local cerebral blood flows did not differ between both groups. With increasing degrees of hypercapnia, global and local cerebral blood flows were gradually elevated in the low-viscosity group (2.8 ml x mmHg(-1) CO2 x 100 g(-1) x min(-1)), whereas they remained unchanged in the high-viscosity group.Changes in blood viscosity do not result in changes of cerebral blood flow as long as cerebral vessels can compensate for these changes by vasodilation or vasoconstriction. However, such vascular compensatory adjustments may be exhausted in their response to further pathophysiologic conditions in blood vessels that have already been dilated or constricted as a result of changes in blood viscosity.